NEEDLE-STICK INJURY: A RISING BIO-HAZARD - Malik, Aeeza; Shaukat, Malik Saleem; Qureshi, Ambrina (Journal of Ayub Medical College Abbottabad, 2012)
Background: Needle stick injury has been identified as the foremost health allied concern and the specialty of dentistry is not an exception. Its incidence can be reduced when a dental practitioner is completely proverbial to the standard cross-infection control measures. This study was intended to assess the knowledge, attitude and practices among the dental practitioners regarding Needle Stick Injuries and associated risk factors. Methods: This survey was carried out in the Oral Surgery Department, Dr. Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Karachi. Dental practitioners of different job categories were conveniently approached by the BDS students. They all were provided with a structured and validated, self-administered questionnaire. Descriptive statistics and Chi-square test was applied with 5% level of significance. Results: All 100 (55 females and 45 males) practitioners agreed to participate in the study. Prevalence of Needle Stick Injury observed was 30% with no significant relationship with the demographic characteristics. Seventy-four percent of the participants were aware of the universal guidelines. Majority (88%) of the dental personnel believed that recapping of needles should be performed soon after use and 53% knew about needle-less safety devices. These injuries were experienced by 30% of the respondents, of which just 28% were reported. Conclusion: Dental practitioners were at high risk of getting Needle Stick Injuries in dental offices. Most of them had knowledge about it but there was lack of practice of universal precautions. Keywords: Needle Stick Injury, Blood Borne Diseases, Dental Practitioners, precaution, infection